Path Life Based on SNR Modeling for Routing Protocol Improvement with Cross Layer Scheme in Wireless Adhoc Network - ., Istikmal; Kurniawan, Adit; ., Hendrawan (International Journal of Engineering and Technology, 2026)
In this paper, we develop a detailed approach modeling to study how channel quality, as represented by the Signal-to-Noise Ratio (SNR), impacts on the path life of the route and the network throughput performance. Based on this fact, we proposed an adaptive algorithm for routing protocol with a cross-layer scheme based on SNR. This proposed scheme is an enhancement of reactive routing protocol Ad-hoc On-demand Distance Vector (AODV), which we call AODV SNR+. We use a combination of the preset SNR threshold and the minimum SNR threshold in the route discovery process. With this combined scheme, the routing protocol can select an appropriate route with quality channel aware and be more adaptive when path break often occur in the network. We compare AODV SNR+ with AODV and AODV SNR-SR (Selective Route). The simulation results showed that AODV SNR+ outperform AODV. We found that AODV SNR+ suitable in dynamic networks, while AODV SNR-SR can gain advantage in high traffic with stable channel quality.
Keywords: Path life; Routing; SNR; AODV; Cross-Layer